ESTIMASI DISTRIBUSI PERGERAKAN DENGAN METODE KEMIRIPAN MAKSIMUM DAN FUNGSI HAMBATAN EKSPONENSIAL NEGATIF (STUDI KASUS KABUPATEN SRAGEN) (FSTPT Indonesia, 2023)
The needs of large vehicle movements certainly require planning a transportation system that can prevent problems such as congestion. The steps that can be taken are to conduct a study of the generation and attraction as well as the movement distribution model in the form of an Origin Destination Matrix (O-D Matrix) which is analyzed by the Gravity Model of the generation-attraction limit and then processed by the EMME/3 program. This study was conducted in Sragen Regency which is divided into 27 zones. The loading of traffic flow results in the road network using the User Equilibrium method. Newton-Raphson calibration was carried out to obtain the value through the use of the Maximum Likelihood (ML) method and the Negative Exponential Resistance Function. This study aims to obtain the parameter, the distribution of traffic movement between zones, and calculate the accuracy of traffic flow using the coefficient of determination (R2). The results of the study obtained a value of 0.079. The total estimated distribution of movement that occurs in Sragen Regency in 2022 is 9893 pcu/hour with the result of the validity test (R2) from the comparison of observation and modeling values of 0.7805. ABSTRAKPemenuhan kebutuhan pergerakan kendaraan yang besar tentu memerlukan perencanaan sistem transportasi untuk mencegah permasalahan seperti kemacetan. Langkah yang dapat dilakukan dengan studi mengenai bangkitan dan tarikan serta model sebaran pergerakan dalam bentuk Matriks Asal Tujuan (MAT) yang dianalisis dengan Model Gravity batasan bangkitan-tarikan lalu diolah dengan program EMME/3. Studi ini dilaksanakan di Kabupaten Sragen yang dibagi menjadi 27 zona. Metode User Equilibrium digunakan untuk pembebanan hasil arus lalu lintas ke jaringan jalan. Kalibrasi Newton-Raphson dilakukan untuk memperoleh nilai ???? melalui penggunaan metode Penaksiran Kemiripan Maksimum (KM) dan Fungsi Hambatan Eksponensial Negatif. Penelitian ini bertujuan untuk mendapatkan parameter ????, besar distribusi pergerakan lalu lintas antar zona, serta menghitung tingkat akurasi arus lalu lintas menggunakan koefisien determinasi (R2). Hasil penelitian diperoleh nilai β sebesar 0,079. Total estimasi distribusi pergerakan yang terjadi di Kabupaten Sragen tahun 2022 adalah 9893 smp/jam dengan hasil validitas (R2) dari perbandingan nilai pengamatan dan pemodelan yaitu 0,7805.